NGAJI ONLINE: Transformasi Ngaji Kitab di Media Sosial - Evi Fitriana; Muhamad Khoiri Ridlwan (ASANKA: Journal of Social Science And Education, 2021)
Social change includes elements of both material and non-material culture. This emphasizes the great influence of material elements of culture on non-material elements. Technological developments cause cultural changes.The digital era has an impact on shifting interest in the search for Islamic knowledge from offline to online systems. Therefore, religious learning becomes easy and practical. The transfer of Islamic religious knowledge in “ngaji online" is not only from the teacher directly by coming to a majlis ta'lim, but can be done through social media. "Ngaji online " on social media must be equipped with controls for the content displayed. The new order that emerges from the activity of "ngaji online" forms a new habitus that adapts to the social conditions of the community. The paradigm of social change theory discusses changes in society and the processes that occur in these changes. The problem in the online Ngaji phenomenon leads to a social fact paradigm that is linked to functional structural theory.